1995
DOI: 10.2527/1995.731236x
|View full text |Cite
|
Sign up to set email alerts
|

Net nutrient flux by visceral tissues of beef steers given abomasal and ruminal infusions of casein and starch.

Abstract: The objective of this study was to quantify changes of net nutrient metabolism by portal-drained viscera (PDV) and liver of four beef steers (253 +/- 7 kg) in response to combinations of ruminal (R) or abomasal (A) infusions of cornstarch (S) and casein (C). The four treatments in a Latin square design were SACA, SACR, SRCA, and SRCR. Steers were fed alfalfa hay (DMI = 4 kg/d) as a basal diet in 12 equal meals delivered every 2 h and they received continuous infusion of S (800 g/d) and C (200 g/d) in 11-d peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
75
1
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 28 publications
16
75
1
7
Order By: Relevance
“…The extent of AA removal by the splanchnic tissues has been shown to vary with level of feed intake (Savary-Auzeloux et al, 2003). The increased NPA of AA observed with increasing DMI in this study is consistent with previous reports in cattle (Huntington et al, 1988;Lapierre et al, 2000) and sheep (Noziè re et al, 2000;Hoskin et al, 2001) and may reflect increased intestinal absorption of AA as a result of increased duodenal flow of dietary, microbial and endogenous AA because of increased available energy (Guerino et al, 1991;Taniguchi et al, 1995). Clark et al (1992) showed that faster rate of passage of feed residues and the microbes out of the rumen at higher intakes resulted in a higher duodenal flow of dietary protein and non-ammonia nitrogen and an increase in microbial protein synthesis.…”
Section: N Balancesupporting
confidence: 82%
See 1 more Smart Citation
“…The extent of AA removal by the splanchnic tissues has been shown to vary with level of feed intake (Savary-Auzeloux et al, 2003). The increased NPA of AA observed with increasing DMI in this study is consistent with previous reports in cattle (Huntington et al, 1988;Lapierre et al, 2000) and sheep (Noziè re et al, 2000;Hoskin et al, 2001) and may reflect increased intestinal absorption of AA as a result of increased duodenal flow of dietary, microbial and endogenous AA because of increased available energy (Guerino et al, 1991;Taniguchi et al, 1995). Clark et al (1992) showed that faster rate of passage of feed residues and the microbes out of the rumen at higher intakes resulted in a higher duodenal flow of dietary protein and non-ammonia nitrogen and an increase in microbial protein synthesis.…”
Section: N Balancesupporting
confidence: 82%
“…One explanation for higher PDV recovery in this study may be partially attributed to a decrease in the absorptive PDV use of AA because of increased available energy substrates. Several reports have demonstrated that greater flow of post-ruminal AA increases the small intestinal OM and starch digestibility (Richards et al, 2002) and increases portal glucose appearance (Taniguchi et al, 1995), and consequently improve AA absorption from the basal diet probably by sparing gut-tissue AA from breakdown. In addition, it was reported that the additional energy supplied by excess AA can improve the absorption of other limiting AA (Schroeder and Titgemeyer, 2008).…”
Section: N Balancementioning
confidence: 99%
“…Em alguns trabalhos, a utilização de fontes de amido de alto escape ruminal favoreceu a deposição de gordura visceral, diminuindo o rendimento de carcaça em bovinos e ovinos de corte (Owens et al, 1986;Taniguchi et al, 1995;Luchiari Filho & Moura, 1998). Possivelmente, a utilização de dietas com alto teor de concentrado ou de ingredientes como a polpa cítrica conferiu vantagens adicionais ao rendimento de carcaça, o que não permitiu a expressão dessa melhora da digestão do amido com a utilização da silagem de grãos de milho úmidos.…”
Section: Resultsunclassified
“…These differences demonstrate the complexity of the regulation of α-amylase and indicate that nutritional influences on enzyme regulation may not be comparable between different species of ruminants. Taniguchi et al (1995) infused casein and starch postruminally in steers and demonstrated that in the presence of casein, the supply of glucose from the portal-drained viscera was increased. This suggested that casein (or protein) may somehow improve intestinal starch disappearance.…”
Section: Intestinal Starch Assimilation Pancreatic α-Amylasementioning
confidence: 99%